2016
DOI: 10.1186/s12917-016-0757-x
|View full text |Cite
|
Sign up to set email alerts
|

Canine distemper virus isolated from a monkey efficiently replicates on Vero cells expressing non-human primate SLAM receptors but not human SLAM receptor

Abstract: BackgroundIn 2008, an outbreak of canine distemper virus (CDV) infection in monkeys was reported in China. We isolated CDV strain (subsequently named Monkey-BJ01-DV) from lung tissue obtained from a rhesus monkey that died in this outbreak. We evaluated the ability of this virus on Vero cells expressing SLAM receptors from dog, monkey and human origin, and analyzed the H gene of Monkey-BJ01-DV with other strains.ResultsThe Monkey-BJ01-DV isolate replicated to the highest titer on Vero cells expressing dog-orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Phylogenetic analysis of the full-length H gene showed that Monkey CYN07-dV [58] and Monkey-BJ01-DV were highly related to other CDV strains obtained from species of the Canidae family in China during this time period. The monkey CDV strains (Monkey-BJ01-DV, CYN07-dV, Monkey-KM-01) possess a number of amino acid-specific substitutions (E276V, Q392R and D435Y) compared to the H protein of CDV occurring in other animals for the same period [57,71]. An additional change from I542F in these monkey strains is also noted from our current analysis.…”
Section: Genetic Analysis Of Cross Species Infectionsupporting
confidence: 61%
See 2 more Smart Citations
“…Phylogenetic analysis of the full-length H gene showed that Monkey CYN07-dV [58] and Monkey-BJ01-DV were highly related to other CDV strains obtained from species of the Canidae family in China during this time period. The monkey CDV strains (Monkey-BJ01-DV, CYN07-dV, Monkey-KM-01) possess a number of amino acid-specific substitutions (E276V, Q392R and D435Y) compared to the H protein of CDV occurring in other animals for the same period [57,71]. An additional change from I542F in these monkey strains is also noted from our current analysis.…”
Section: Genetic Analysis Of Cross Species Infectionsupporting
confidence: 61%
“…The majority of CDV strains isolated from Canidae have tyrosine at site 549, whereas CDV strains from other carnivore families mostly have histidine [76]. The specificity with which CDV-H interacts with SLAM and its potential as a determinant of host range have been investigated [71,76,82,83,84,85,86]. Amino acid residues Y525, D526 and R529 of CDV-H have been identified by site-directed mutagenesis to interact with SLAM [85].…”
Section: Virus Adaption To Cell Entry Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLAM has known as one of receptor against morbilliviruses and is used as a gate for viral entry because it is expressed on the surface of lymphocytes [ 12 ]. In this study, new Vero cells expressing dSLAM gene were constructed to isolate field CDV circulating in Korean dog population as other researchers constructed cells expressing dSLAM gene [ 10 20 ]. We successfully isolated only one virus in Vero/dSLAM cells from 17 suspected samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the essential cause can be the substitutions in the isolated H protein and the CDV H protein. Moreover, while the amino acid sequence identity of the dog SLAM and the monkey SLAM is only 63.6%; the Monkey-BJ01-DV strain is able to replicate itself on the Vero cells expressing the SLAM receptors and originating from dogs as efficiently as the Vero cells which originate from monkey SLAM [101], indicating a potential cross-species event.…”
Section: Main Textmentioning
confidence: 99%